Mobile phones and wrong numbers: how Maasai agro-pastoralists form and use accidental social ties in East Africa - Timothy D. Baird (Resilience Alliance, 2021)
Mobile phones are recognized as important new tools for rural development in the Global South, but few studies have examined how phones can shape social networks. This study documents a new type of social tie, enabled by mobile phones, that to our knowledge has not previously been discussed in academic literature. In 2018, we discovered that Maasai pastoralists in northern Tanzania create new social ties through wrong numbers, a phenomenon with implications for theory on social networks and path dependency. We used a mixed ethnographic and survey-based design to examine the following: (1) the conditions under which wrong number connections (WNCs) are made; (2) the incidence of these connections in the study area; and (3) the association between WNCs and multiple livelihood strategies. Working in 10 rural communities in Tanzania, we conducted 16 group interviews with men about their phone use and found that WNCs are diverse and can provide households with important information, resources, and opportunities from an expansive geographic area. (Nine separate interviews with groups of women revealed that women do not create WNCs.) Based on early qualitative findings, we designed and conducted a standardized survey with 317 household heads. We found that 46% of respondents have had WNCs. Furthermore, multivariate regression models show a significant association between WNCs and the controversial practice of leasing land in one district. Taken together, our findings show that WNCs can be seen as innovations in social networking that reduce path dependency, increase the range of potential outcomes, and hold important implications for rural livelihoods in East Africa.